PERBANDINGAN KADAR KREATININ DAN ASAM URAT PADA SERUM DAN URIN PENDERITA HIPERTENSI DAN NORMOTENSI - Octviani, Putri (LPPM Universitas Negeri Jakarta, 2015)
ABSTRACT Hypertension is an increase of blood pressure over 140/90 mmHg. Hypertensionin along period of timecaninterfere withkidney function. Impaired kidney functioncan be caused byhigh levelsof uricacidin the bloodthatis directly associatedwithperipheralvascular resistanceandrenalvascular. Measurement ofrenal functioncan be measuredbycreatininetest, becauseconcentrations in serumandurineexcretionin24 hoursis relativelyconstant. The aim of this research was to measure and compare creatinine and uric acid on serum and urine in hypertensive and normotensive. The parameters were measured by Mindray BS-300 clinical chemistry analyzer. Ex Post Facto used as method and Cross- sectional used as design. A total of 36 blood and urine samples collected from Hypertensive (N1=18) and normotensive (N2=18) from February to March 2014. SPSS 16.0 was used to analyze the datas, t-test was used to compare value of creatinine urine and uric acid serum while U Mann-Whitney test was used to compare value of creatinine serum. The result of this research showed that the mean value of creatinine serum was 0.80 mg/dL in hypertensive and 0.86 mg/dL in normotensive (p=0.14). The mean value of creatinine urin was 87.28 mg/dL in hypertensive and 74.47 mg/dL in normotensive (p=0.35). The mean value of uric acid serum was 4.06 mg/dL in hypertensive and 4.5 mg/dL in normotensive (p=0.41). The resultsofthe urineuricacidwere foundnegativeofthe presence ofuricacid crystals.In conclusion, there was no different of creatinine and uric acid on serum and urine in hypertensive and normotensive. Keywords: hypertension, normotensive, creatinine, uric acid